Anatomical and Microsurgical Implications in Total and Midarm Transplantation - Iglesias, Martin; Salazar-Hernández, Fernanda; Ramírez-Berumen, María F.; Butrón, Patricia; Alberú-Gómez, Josefina; Leal-Villalpando, Rafael P.; Zamudio-Bautista, Jorge; Acosta, Victor; Jauregui-Flores, Luis A.; Espinosa-Cruz, Verónica; Vázquez-Lamadrid, Jorge; González-Sánchez, Judith; Hinojosa, Carlos A.; Laparra-Escareño, Hugo; Montejo-Vargas, Juan; Macias-Gallardo, Julio (Journal of Reconstructive Microsurgery Open, 2017)
Background Arm transplantations are performed less frequently than forearm and hand transplantations. We present the surgical and microsurgical technique and its relationship with the clinical results in a patient with bilateral arm transplantation. Methods A 51-year-old male patient underwent bilateral arm transplantation in October 2015. The right arm was transplanted at the glenohumeral joint. The vascular repair was at the axillary level, and the nerves were repaired at their origin. The total ischemia time was 3 hours and 48 minutes. The left arm was transplanted at the midhumeral level; all muscles were completely transplanted. The nerves were repaired at the distal third of the arm. Additionally, terminolateral neurorrhaphy was performed from the donor musculocutaneous nerve to the recipient radial nerve. The total ischemia time was 6 hours and 35 minutes. Results At 15 months posttransplantation, the right shoulder had an abduction of 90 degrees and muscle strength of M4; flexion of 100 degrees and M4; internal and external rotation of M1; elbow flexion of 120 degrees and M3; elbow extension of M5; pronosupination of M2; and wrist extension of M2. There was no mobility in the fingers. The left transplanted limb had total elbow flexion and extension of M5, pronosupination of M2, wrist extension of M4, and finger flexion of M2. Both extremities had thermal sensitivity that allowed discrimination of cold and heat with residual deep pressure. Conclusion Although the functional results of arm transplantation are so far unknown, they may be considered beneficial compared with the devastating disability caused by arm amputation.
Keywords: arm transplantation; vascularized composite allotransplantation; hand transplantation